Convocation, Northeast Missouri State Teachers College, Kirksville, Mo., August 04, 1921 - Northeast Missouri State Teachers College (Kirksville, Mo.) (1921)
This convocation program shows the class roll on August 04, 1921 at the Northeast Missouri State Teachers College in Kirksville, MO.